Personal project management: a framework for organizing life and achieving goals (Research, Society and Development, 2020)
Project management has become increasingly consolidated in companies, as it seeks the continuous improvement of processes, quality in deliveries, compliance with agreed deadlines and costs. In this way, through the transformations of business and technology, new approaches and tools emerge daily improving more and more the way of managing projects. In this scenario, we find many contents, methodologies, frameworks and case studies, aimed at organizational projects. However, in our life we face several challenges and activities of daily life, which can be seen as personal projects and, in the same way, can be managed. From this perspective, taking as context the difficulties that the vast majority of individuals encounter to organize their lives, a framework for personal project management has been developed. The Framework developed, aims to provide individuals the ability to reflect on their achievements, dissatisfaction and goals, as well as transform the way to see various wills and dreams, as true personal projects. The Framework includes a conceptualization phase on project management and three practical steps composed of: Swot Analysis intended for personal life; Project Mind Mapping and the daily Kanban, adapted for the weekly calendar. The Framework was applied to 10 people of different ages and professions, with the aim of identifying the main needs of life planning and daily organization. Using the Framework allows individuals to increase their performance and productivity by carrying out personal projects, which become project managers of their lives.